The Role of Finance on Achieving Companies Goals - Mehmeti, Fatmir; Mustafa, Pleurat (European Journal of Economics and Business Studies, 2015)
The role of companies on economic development, in increasing employment and improving the welfare of its citizen by offering various products and services is continually increasing and having a higher significant role, especially in today’s times of economic globalization that we have on. Different companies, whether privet or public have their own goals and objectives to achieve where their main goal is profit maximization. The basic element to achieve company’s goal and objective is to ensure and manage financial funds. Business owners determent in the accomplished of objectives, including financial objectives, based on the high competition environment that is persistent and each time more aggressive, in order to survive and to achieve their foreseen goals, the company must continually make investments in (equipment, land, buildings, staff training, new staff engagement, marketing, etc. ), and in order to make these investments possible the company needs to achieve these financial tools, successful management of funds, where the auditing plays a significant role in the successful management. The financial system is undoubtedly a correct catalyst or better yet a laboratory where economic developments take the right shape and form. Complexity and size of organization makes it impossible for the higher management to control each individual if the organization is running its activity in the most effective way. Financial statements are a passport of companies where the management, accounting and auditors are highly linked. The aims of these financial statements are intended to provide reasonable assurance regarding the achievement of key objectives such as: Effectiveness and efficiency of operations, reliability of financial reporting and management, compliance with laws and regulations and preservation of assets. In this paper we will focus on the sources of financial funds of companies, successful management of finances as a basic element of meeting the objectives and internal and external audit as a key element that ensures the success of companies.